Addressing meniscal deficiency part 1: An umbrella review of systematic reviews and meta‐analyses on meniscal allograft transplantation - Kevin A. Wu; Lulla V. Kiwinda; Aaron D. Therien; Christian J. Castillo; Stephanie Hendren; Jason S. Long; Annunziato Amendola; Brian C. Lau (Journal of Experimental Orthopaedics)
Abstract Purpose Meniscal injuries are common in the young and active population. There is increasing utilization of surgical interventions like meniscal allograft transplantation (MAT) to restore the protective function of menisci following injury leading to meniscal deficiency. Extensive research and publications exist on the management of meniscal injury and the sequalae of meniscal deficiency. However, a comprehensive synthesis of the existing evidence through an umbrella review is lacking. This study aims to fill this gap by providing a current examination of the literature on MAT. Methods A comprehensive search was conducted in the MEDLINE, Embase and Scopus databases to identify relevant systematic reviews and meta‐analyses. Studies were screened based on predefined inclusion and exclusion criteria. The quality of the included studies was assessed using the AMSTAR‐2 tool. Results A total of 41 studies were included in the review, with most published within the last decade. The majority of studies (56.1%) received a ‘Critically Low’ confidence rating, 26.8% were rated as ‘Low’, and only 14.6% were rated as ‘High’ confidence. From the included studies, 51.2% reported on PROMs, with the Lysholm score being the most common. Transplant failure and reoperation rate were reported in 34.1% and 19.5% of studies respectively. Studies on MAT reported favourable short‐term outcomes in terms of patient‐reported outcome measures (PROMs) but were limited by the lack of randomized control trials and consistent comparison groups. Conclusions This umbrella review highlights an increase in interest in MAT but underscores the need for higher‐quality reviews with standardized reporting and rigorous methodologies. Future research should focus on long‐term outcomes, optimal surgical techniques, patient selection criteria and risk factors for transplant failure. There is also a need for more studies focusing on MAT in pediatric populations. Overall, this review provides a comprehensive assessment of the current state of research in MAT and identifies areas for improvement in future studies. Level of Evidence Level IV.